Revisiting the values in Moral Education for Malaysian schools - Hoon, Chang Lee (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
In 1983, the Moral Education (ME) subject was first implemented as a core subject in primary one to non-Muslim pupils, whilst the Muslim pupils attended Islamic Education. It was implemented in stages on a year-by-year basis until form five at secondary school by 1993. The first ME syllabus covered 16 core values and 64 sub-values. In 2000, the ME syllabus was revised and the values were then reduced to 36. In 2010, the Standards Primary School Curriculum (SPSC) was introduced. As such, the ME syllabus was further revamped and it now consisted of 14 values. As the SPSC is being implemented in stages on year to year basis, it can be expected that there will be changes to the curriculum for secondary schools. This article intends to revisit the values in the ME syllabus by analysing official documents relevant to ME for Malaysian schools.